Human Embryonic Stem Cell-Based Cardiac Regeneration: A ‎Quantitative Analysis for Tissue Engineering and Biomedical ‎Advancements - PG, Gayathri; Nair, Dr. Ambika R. (International Journal of Basic and Applied Sciences, 2025)
This research paper examines the efficiency of human embryonic stem cell (hESC)-derived ‎cardiac tissue engineering in promoting cardiac restoration through scientific & medical ‎integration. The objective is to assess the capability of h ESC-derived cardiomyocytes to ‎improve heart function based on differentiation efficiency and functional outcomes from ‎available data chosen from research studies. A systematic analysis of secondary data derived ‎from studies of Liu et al. (2024), which reported 88% ± 3% differentiation efficiency on ‎graphene scaffolds and 25% ± 6% ejection fraction improvement in rat models, and Chong et ‎al. (2014), demonstrating 70% ± 5% cell integration has been analysed. It falls under the ‎purview of examining cellular differentiation processes and cardiac repair treatments in ‎health sciences. Statistical assessments (ANOVA, p < 0.001) validate reliability, and graphene ‎scaffolds perform better than collagen (82% ± 4%) and PLGA (75% ± 5%). The research ‎highlights the ability of hESCs to bridge mechanistic understanding and therapeutic ‎innovation, opening doors to large-scale cardiac therapy. Ethical and legal concerns, notably ‎embryo use regulations, require compliance with ISSCR guidelines. Future studies should aim ‎to accumulate primary data, new biomaterials (e.g., carbon nanotubes), and large animal ‎models (e.g., pigs) to maximize clinical translation and tackle risks such as ventricular ‎tachyarrhythmias‎.
Keywords: Cardiac Restoration; Ethical Considerations; Human Embryonic Stem Cells; Tissue ‎Engineering; Regenerative Medicine